Jugular venous desaturation and outcome after head injury. Issue 6 (June 1994) - Gopinath, S P; Robertson, C S; Contant, C F; Hayes, C; Feldman, Z; Narayan, R K; Grossman, R G
Abstract : Early experience with continuous monitoring of jugular venous oxygen saturation (SjvO2) suggested that this technology might allow early identification of global cerebral ischaemia in patients with severe head injury. The purpose of the present study was to examine the relationship between episodes of jugular venous desaturation and neurological outcome. One hundred and sixteen severely head-injured patients had continuous monitoring of SjvO2 during days 1-5 after injury. Episodes of jugular venous desaturation (SjvO2 < 50% for more than 10 minutes) were prospectively identified, and the incidence of desaturation was correlated with neurological outcome: 77 episodes of desaturation occurred in 46 of the 116 patients; 27 had one episode and 19 had multiple episodes of desaturation. The causes of these episodes were systemic (n = 36), cerebral (n = 35), or both (n = 6). Most of the episodes were less than 1 hour in duration, and it is probable that many of them would not have been detected without continuous measurement of SjvO2. Episodes of desaturation were most common on day 1 after injury, and were twice as common in patients with a reduced cerebral blood flow as in patients with a normal or elevated cerebral blood flow. The occurrence of jugular venous desaturation was strongly associated with a poor neurological outcome. The percentage of patients with a poor neurological outcome was 90% with multiple episodes of desaturation and 74% in patients with one desaturation, compared to 55% in patients with no episodes of desaturation. When adjusted for all co-variates that were found to be significant, including age, Glasgow coma score, papillary reactivity, type of injury, lowest recorded cerebral perfusion pressure, and highest recorded temperature, the incidence of desaturation remained significantly associated with a poor outcome. Although a cause and effect relationship with outcome cannot be established in this study, the data suggest that monitoring SvO2 might allow early identification and therefore treatment of many types of secondary injury to the brain.